Optimalisasi Peran Pendidikan dan Sosialiasi Manajamen Keuangan dalam Pemberdayaan Masyarakat Desa Karangsari - Putranto, M. Dzaky; Sumitro, Wilal; Rosid, Abdul; Sari, Indaah Kumala; M. Zainil; Nanda A, Desca; Trijaya, M. Kurnia; Aisah, Siti; Inderawan P, Danang; Rubiyanto, Cahyo Wisnu (Universitas Muhammadiyah Yogyakarta, 2025)
This community service activity aims to provide tangible benefits through various programs focused on education, financial management awareness, as well as environmental and health concerns. The activity was conducted in Karangluas Hamlet, Karangsari Village, Sapuran Sub-district, Wonosobo Regency, for a duration of one month. The methods employed included interviews, focus group discussions (FGDs), and community outreach involving local residents. The educational program focused on improving literacy and academic skills among children, as well as empowering the community through knowledge-based training. The financial management awareness program aimed to enhance the community's understanding of personal and small business financial management in order to support economic self-sufficiency. In addition, environmental and health awareness initiatives were carried out through cleanliness campaigns, reforestation efforts, and education on healthy lifestyles, with the goal of raising public awareness regarding the importance of a clean environment and healthy living. The results of this community service program indicated an increase in public understanding and active participation in the three main areas. Through the implementation of these programs, it is expected that the community will be able to apply the acquired knowledge in their daily lives, thereby contributing to a sustainable improvement in quality of life.